A Two Stage Of Concurrent Dual-Band Low Noise Amplifier Using Current-Reused With Hi-Pass And Lo-Pass Matching Technique - Azman, Ahmad; Abdul Rani, Othman; Zahriladha, Zakaria; Kamil, Pongot (JATIT & LLS, 2016)
This paper presents the design and analysis of a dual-band low noise amplifier (LNA) at 2.4 GHz and 5.75 GHz for IEEE 802.11 a/b/g applications. This LNA proposed current-reused topology and presented new Hi-Pass and Lo-Pass matching technique network at the two stage common-source transistor. The LNA used GaAs HEMT transistor to improve the gain and noise figure (NF) matched concurrently at the two frequency bands. The simulation results showed a high gain |S21| of 36.093 dB and 23.152 dB and low NF of 0.735 dB and 0.530 dB for center frequency of 2.4 GHz and 5.75 GHz. The supply voltage for LNA is 2V. Simulation of the design was performed with the Advanced Design System (ADS) software.